DINA: Development Model Physical Activity of Dance Intensive Nimble Physical Activity for Children Aged 9-10 Years - Dina Firda Maula; Putra, Ranu Baskora Aji (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2024)
Physical activity is vital for children to improve their motor skills and overall fitness. This study aimed to develop the Dance Intensive Nimble Activity (DINA), a physical activity model combining trending TikTok dances with short, high-intensity mini-games. The ADDIE model (Analyze, Design, Develop, Implement, Evaluate) guided the development. The study involved 68 children aged 9-10 years across Central Java and Yogyakarta schools, with data collected through observations, questionnaires, and documentation. Expert validation rated DINA as "Very Valid" (mean score 3.76/4), while children's responses showed high enthusiasm (mean score 3.60/4). DINA was easy to follow, engaging, and beneficial in enhancing motor skills, fitness, and cognitive function. The combination of fun music, simple moves, and ice-breaking elements made DINA enjoyable for children, promoting positive feelings and motivation. In conclusion, DINA is an effective and practical alternative physical activity model for children aged 9-10.